ASSESSMENT OF ANTHROPOMETRIC INDICES, FOOD CONSUMPTION PATTERN AND IRON STATUS OF ADOLESCENT GIRLS ATTENDING SECONDARY SCHOOLS IN SABON GARI LGA, KADUNA STATE, NIGERIA - Abdulazeez Muhammad, Aishah; Samuel Ndidi, Uche; Shuaibu, Muhammad Nasir; Adamu, Hussaina; Sadiq Abubakar, Fatima (FUDMA JOURNAL OF SCIENCES, 2025)
This study was cross-sectional study where adolescent girls between 10 and 18 years were selected using a multistage sampling technique. The anthropometric indices, food consumption patterns and iron status of the school girls attending secondary schools in Sabon Gari Local Government Area, Kaduna State, Nigeria was assessed. Serum iron, ferritin, hemoglobin, total iron binding capacity (TIBC) and transferrin saturation (TSAT) were measured using standard procedures. The results of the study showed that majority of the girls are mid (14-16 years) adolescents. BMI-for-age showed that 81.7% of the girls have normal BMI-for-age, 6.1% were overweight and 3.9% were obese. Cereals, soft drinks and sugar are highly consumed; legumes, milk and products, fruits and vegetables, tea and beverages are moderately consumed while meat, fish and sea foods and eggs have low consumption pattern. Dietary diversity showed that 81.1% did not meet minimum dietary diversity while 18.9% met the minimum dietary diversity. Mean serum ferritin of adolescent girls is 34.4±2.2ng/ml, hemoglobin is 10.08±1.7g/dl, mean serum iron is 55.85±9.2µg/dl, mean TIBC is 322.98±22.7, while mean TSAT is 24.73±12.1%. Increase in adolescents age, (p=0.03), increase in family size (p=0.041) and low education level of parents (p=0.047) have significant association with serum ferritin. Attending public school (p=0.041) and low education level of parents (p=0.03) have significant association with hemoglobin. The findings of this study show that iron deficiency anemia is of moderate public health significance while anemia is of high public health significance among adolescent girls attending secondary schools in Sabon Gari LGA of Kaduna State.
Keywords: Anemia; Adolescent school girls; BMI-for-age; Dietary pattern